EXPERIMENTAL INVESTIGATION OF THE POPULATION DENSITIES OF LOWEREXCITED STATES OF NEON (Journal of Sciences, Islamic Republic of Iran)
Many studies employing various methods have been carried out into the number densities of excited atoms in electrical discharges with inert gases [1,2,3], but the ranges of the discharge current and gas pressure is very limited in them all. In this work, the population densities of 3S, 3s' of neon have been investigated using the atomic absorption method. Since the discharge current and gas pressure have marked effects on the variation of these densities, the pressure range of 0.1-15 m. bar and currents up to 30 mA have been used